2018
DOI: 10.1039/c8ra05806g
|View full text |Cite
|
Sign up to set email alerts
|

Coptisine suppresses tumor growth and progression by down-regulating MFG-E8 in colorectal cancer

Abstract: Treating colorectal cancer (CRC) continues to be a clinical challenge. Coptisine, an alkaloid derived from Coptis chinensis Franch. shows toxic effects on CRC cells, but its underlying mechanism remains elusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…For example, Han et al [ 19 ] demonstrated that coptisine induced apoptotic cell death through reactive oxygen species (ROS) production, a decline of mitochondrial membrane potential (MMP, ΔΨm), and activation of mitochondrial-associated apoptosis in human colon cancer. More current reports have suggested that coptisine inhibited cell growth, migration, and invasion via regulation of the phosphoinositide 3-kinases (PI3K)/Akt pathway in colorectal and pancreatic cancers [ 23 , 24 ]. Although several studies have shown that coptisine had anticancer activity against HCC, the underlying mechanism was unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Han et al [ 19 ] demonstrated that coptisine induced apoptotic cell death through reactive oxygen species (ROS) production, a decline of mitochondrial membrane potential (MMP, ΔΨm), and activation of mitochondrial-associated apoptosis in human colon cancer. More current reports have suggested that coptisine inhibited cell growth, migration, and invasion via regulation of the phosphoinositide 3-kinases (PI3K)/Akt pathway in colorectal and pancreatic cancers [ 23 , 24 ]. Although several studies have shown that coptisine had anticancer activity against HCC, the underlying mechanism was unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have established that coptisine exerts ameliorative effect on cancer in in vivo model. Cao et al reported that coptisine (30‐90 mg/kg, i.p, once daily for 14 days) could prevent tumour development by inhibiting MFG‐E8, MMP‐2/9, N‐cadherin, vimentin and Snail expressions and increase E‐cadherin expression in HCT116‐challenged nude mouse . Interestingly, in the same xenograft tumour model, administration of coptisine (50‐150 mg/kg, oral, once daily for 25d) decreased serum level of tumour markers such as CEA, CA119 and CYFRA, and this effect was related to the changed mRNA expressions of TNF‐β, KRAS, ERK and p53 .…”
Section: Anti‐cancer Propertymentioning
confidence: 98%
“…Coptisine (0–25 μmol/L, 24 hours) was demonstrated to inhibit the viability, adhesion and migration of HCT116 cells and the expressions of MMP‐3 and MMP‐9. It also down‐regulated PI3K and Akt expression as well as altered the downstream EMT markers such as E‐cadherin, N‐cadherin, vimentin and Snail . Apoptosis plays a vital role in the progression of multiple cancers and basically activated by a mitochondria‐induced intrinsic or a death receptor‐induced extrinsic pathway, both of which are correlated with mitochondria and Bcl‐2 family anti‐apoptotic proteins .…”
Section: Anti‐cancer Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…However, work on coptisine chloride also focused on the medicinal activities, such as the antitumor, anti-inflammatory, anti-hypercholesterolemic activity, and the distribution in rat. [31][32][33][34][35] To date, no herbicidal activity has been reported on worenine chloride and coptisine chloride.…”
Section: Summary Of Herbicidal Activitymentioning
confidence: 99%